2019
DOI: 10.1123/ijspp.2018-0717
|View full text |Cite
|
Sign up to set email alerts
|

Development of an On-Water Graded Exercise Test for Flat-Water Sprint Kayak Athletes

Abstract: Purpose: To determine the reliability and validity of a power-prescribed on-water (OW) graded exercise test (GXT) for flat-water sprint kayak athletes. Methods: Nine well-trained sprint kayak athletes performed 3 GXTs in a repeated-measures design. The initial GXT was performed on a stationary kayak ergometer in the laboratory (LAB). The subsequent 2 GXTs were performed OW (OW1 and OW2) in an individual kayak. Power output (PWR), stroke rate, blood lactate, heart rate, oxygen consumption, and rating of perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
3
17
1
Order By: Relevance
“…Indeed, this extensive experience was considered important for achieving optimal reliability and validity. In fact, in connection with previous investigations employing a protocol that differed only slightly from our own with respect to the number, duration, and intensity of incremental steps, the reliability and validity of measurements of HR, oxygen consumption (VO 2 ), blood lactate and stroke rate were all reported to be acceptable to excellent (Carrasco Páez et al, 2010 ; Winchcombe et al, 2019 ; Matzka et al, 2021 ).…”
Section: Methodssupporting
confidence: 64%
“…Indeed, this extensive experience was considered important for achieving optimal reliability and validity. In fact, in connection with previous investigations employing a protocol that differed only slightly from our own with respect to the number, duration, and intensity of incremental steps, the reliability and validity of measurements of HR, oxygen consumption (VO 2 ), blood lactate and stroke rate were all reported to be acceptable to excellent (Carrasco Páez et al, 2010 ; Winchcombe et al, 2019 ; Matzka et al, 2021 ).…”
Section: Methodssupporting
confidence: 64%
“…Training in different zones strengthens the connected processes to provide energy, allowing the athlete to perform better during the related load conditions. While previous groups concluded that there are differences between onergometer and on-water kayaking with this regard Hunter, Cochrane, & Sachlikidis, 2008), ergometer training is still a widely used tool during winter and to study the different aspects of kayaking (Jones & Peeling, 2014;Michael, Rooney, & Smith, 2008;Winchcombe et al, 2019). In our exercise stresskayak ergometer setting by using the vita maxima and vita sub-maximal test load profiles, we were able to eliminate anomalies resulting from individual differences in the metabolic background, thus producing physical stress equal for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier reports showed the feasibility and reproducibility of various measurements during training (Fleming, Donne, Fletcher, & Mahony, 2012;Tay & Kong, 2018;, in laboratory environments and on-water (Bjerkefors et al, 2019;Steeves et al, 2019;Winchcombe, Binnie, Doyle, Hogan, & Peeling, 2019). However, sophisticated parallel data collecting, processing, and feedback systems still need to be established for kayakers.…”
Section: Introductionmentioning
confidence: 99%
“…The time for each change in direction was extracted using the GPS-data. Previous investigations involving on-water incremental step testing in sprint kayakers showed acceptable to excellent reliability and validity of measurements of HR, oxygen uptake, blood lactate and stroke rate [18,19] and strong correlations with performance [17].…”
Section: Incremental Testingmentioning
confidence: 99%